ANALISIS KESULITAN SISWA DALAM MENULIS CERITA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SDN CIMONE 5 KOTA TANGERANG - Nur Afifah Oktaviani; Aam Amaliyah; Asih Rosnaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Difficulties in writing are difficulties in the process of writing and spelling which involve physical aspects in expressing the results of expressions, thoughts, feelings, and ideas in written form. This study aims to determine the writing difficulties experienced by third grade students at SDN Cimone 5 Tangerang City. This study used a qualitative descriptive method using data collection techniques in the form of writing test tests, interviews with students and teachers, observation and documentation. Checking the validity of the data using triangulation. Data were analyzed through the steps of data collection, data reduction, data presentation and drawing conclusions. Respondents in this research amounted to 6 people, namely 1 teacher and 5 students from grade 3. Based on the results of the research that was too slow in writing, wrong direction in writing letters and numbers, too skewed, inconsistent spacing between letters, dirty writing, imprecise in following horizontal lines, the shape of letters or numbers is illegible, the pencil pressure is not right (too thick or too thin), the size of the writing is too big or too small, and the shape is upside down can affect students' difficulties in writing